Psychological flexibility at school. Toward learning environments more apt to the challenge of not leaving anyone behind - Ferrara, Domenico (Form@re - Open Journal per la formazione in rete, 2025)
This contribution proposes an analysis of some of the possible school context avoidance processes potentially related to dropping out through the filter of the psychological flexibility model. In it, human suffering is observed primarily as the result of attempting to avoid difficult internal experiences related to life contexts, and, in doing so, to act in ways that distance the suffering subject from the most meaningful dimensions of his or her own experience. The model identifies six processes of inflexibility involved in this outcome and, in parallel, six processes of flexibility that can be fostered and supported through specific contextual transformations, especially related to the verbal context of experience. These processes and some of their possible implications in reducing school context avoidance are therefore presented. The validity of an intervention based on psychological flexibility to reduce school avoidance will have to be experimentally verified. La flessibilità psicologica a scuola. Verso contesti di apprendimento più adatti a non lasciare nessuno indietro. Questo contributo propone un’analisi di alcuni dei possibili processi di evitamento del contesto scolastico potenzialmente connessi all’abbandono attraverso il filtro del modello della flessibilità psicologica. In esso, la sofferenza umana è osservata soprattutto come il risultato del tentativo di evitare esperienze interne difficili connesse ai contesti di vita, e, nel farlo, di agire in modi che allontanano il soggetto che soffre dalle dimensioni per sé più significative della propria esperienza. Il modello identifica sei processi di inflessibilità coinvolti in questo esito e, parallelamente, sei processi di flessibilità che possono essere favoriti e supportati attraverso specifiche trasformazioni contestuali, soprattutto connesse al contesto verbale dell’esperienza. Si presentano quindi tali processi e alcune possibili loro implicazioni nella riduzione dell’evitamento del contesto scolastico. La validità di un intervento basato sulla flessibilità psicologica per ridurre l’evitamento scolastico dovrà essere sperimentalmente verificata.